A study of the collection development practices of selected government hospital libraries in Quezon City - Perocho, Kathrina T. (2004)
This study was conducted to determine the collection development practices of six government hospital libraries in Quezon City and the factors that affect the collection development activity. To do this, the following components of the collection development process were closely analyzed - community analysis, formulation of collection development policies, selection and acquisition, collection evaluation and weeding.